Quality of life of children and adolescents with spina bifida - Glamočak Sandra; Uzelac Jovana; Golubović Špela (Association of Nurses Technicians and Midwives, 2023)
Quality of life is a construct that often engages the research community. Examining this construct is of particular importance for individuals with disabilities, chronic illnesses, as well as those with various impairments and disorders. Investigating the quality of life in the population of children and adolescents with spina bifida is particularly significant due to the wide range of challenges these individuals face. This study aims to review relevant literature to identify key factors influencing the quality of life of children and adolescents with spina bifida, with the goal of gaining a deeper understanding of their overall experiences and quality of life. Data from the literature were collected using the PubMed and Google Scholar databases. Literature search, analysis, and comparison of results within the research were conducted based on keywords: spina bifida, myelomeningocele, quality of life, health-related quality of life, children, and adolescents. Based on the review of research results, it can be concluded that the quality of life of children and adolescents with spina bifida is significantly compromised across various dimensions of this construct, and the combined presence of different factors significantly influences the quality of life of this population.